2022
DOI: 10.1055/a-1920-0758
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Postoperative Care Pathway to Reduce Readmissions following Endoscopic Transsphenoidal Pituitary Surgery: Improving Quality of Patient Care

Abstract: Background: Thirty-day unplanned readmission following endoscopic transsphenoidal pituitary surgery (ETPS) occurs in up to 14% of patients. Delayed hyponatremia is one of the most common causes, accounting for 30% of readmissions and often occurs within 1 week of surgery. The authors prior retrospective review identified endocrinology follow up as protective factor. Objectives: Implementation of a multidisciplinary post-operative care pathway (POC pathway): (a) to reduce 30-day hospital readmissions followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Importantly, hyponatremia and electrolyte abnormalities were the most common reasons for readmission while benign headache was the most common discharge diagnosis, findings corroborated by Silva et al 10 Hyponatremia has been recognized as a leading contributor to unplanned readmissions. [12][13][14] There has been mixed success with implementing postoperative endocrine monitoring care pathways with some groups reporting improvements in 30day readmission 15 and others reporting improved rates of identifying patients with hyponatremia, but no reduction in 30-day readmissions. 16 In a query of the National Readmissions Database, Rivzi et al found that readmissions following ESBS were associated with a median hospitalization cost of $7723 (range: $5503-$14,748).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, hyponatremia and electrolyte abnormalities were the most common reasons for readmission while benign headache was the most common discharge diagnosis, findings corroborated by Silva et al 10 Hyponatremia has been recognized as a leading contributor to unplanned readmissions. [12][13][14] There has been mixed success with implementing postoperative endocrine monitoring care pathways with some groups reporting improvements in 30day readmission 15 and others reporting improved rates of identifying patients with hyponatremia, but no reduction in 30-day readmissions. 16 In a query of the National Readmissions Database, Rivzi et al found that readmissions following ESBS were associated with a median hospitalization cost of $7723 (range: $5503-$14,748).…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia has been recognized as a leading contributor to unplanned readmissions 12–14 . There has been mixed success with implementing postoperative endocrine monitoring care pathways with some groups reporting improvements in 30‐day readmission 15 and others reporting improved rates of identifying patients with hyponatremia, but no reduction in 30‐day readmissions 16 …”
Section: Discussionmentioning
confidence: 99%
“…• After the implementation of the MDT protocol, there was a reduction in laboratory studies per patient (55.66 vs. 18.82, p < 0.001), which corresponded to a cost reduction of USD 255.95 per patient • There was a decrease in the number of patients treated with desmopressin (21.4% pre-protocol vs. 8.9% post-protocol, p = 0.04) • All post-protocol patients requiring desmopressin at discharge were identified by 48 h; there was no change in length of stay or need for hydrocortisone post-operatively between the two groups, neither in rates of 30-day readmission Ghiam 2022 J Neurol Surg B Skull Base (PMID: 36393882) [38] Retrospective study 542 patients: 409 pre-protocol vs. 133 post-protocol…”
Section: Benefits Of the Pituitary Mdt/ptcoementioning
confidence: 99%
“…Previously, Carminucci et al reported that the introduction of Pituitary MDT reduced the length of hospital stay post-operatively from a median of 3 to 2 days without compromising outcomes [ 37 ]. Other studies showed that post-operative follow-up by an endocrinologist reduced the risk of 30-day readmission after surgery [ 38 , 39 ]. Cerebrospinal fluid leakage rates after transsphenoidal surgery have decreased since the introduction of a multidisciplinary surgical skull base team in a high-volume Swedish centre [ 40 ].…”
Section: Benefits Of the Pituitary Mdt/ptcoementioning
confidence: 99%
“…Pituitary patients are managed in a multi-disciplinary fashion and thus are a prime example of care delivered by a combination of medical and surgical specialities, offering rich datasets to study this patient group and their management. Patient pathway research across the pituitary MDT has shown to improve safety (19), however, this multidisciplinary care involves a range of users generating data, resulting in a heterogeneous dataset spread across multiple aspects of the EHR. This can make it challenging to identify and extract data for audit or research manually and is a barrier to automating collection of such data (9).…”
Section: Introductionmentioning
confidence: 99%